2018
DOI: 10.1186/s12913-018-3175-x
|View full text |Cite
|
Sign up to set email alerts
|

Policies and clinical practices relating to the management of gestational diabetes mellitus in the public health sector, South Africa – a qualitative study

Abstract: BackgroundWomen with a prior gestational diabetes have an increased lifetime risk of developing type 2 diabetes. Although post-partum follow-up for GDM women is essential to prevent progression to type 2 diabetes, it is poorly attended. The need for health systems interventions to support postpartum follow-up for GDM women is evident, but there is little knowledge of actual current practice. The aim of this study was to explore current policies and clinical practices relating to antenatal and post-natal care f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 54 publications
(76 reference statements)
3
29
1
5
Order By: Relevance
“…In the current study, the public health system was providing poor quality of care and yielding poor health outcomes due mainly to weak leadership and fragmentation of services at the implementation level. Leadership deficits and fragmentation of public healthcare services has also been observed in other South African studies [46][47][48] and research in Gauteng [49] showed that approximately 75% of randomly-selected participants indicated that they were no longer utilising public healthcare services due to the perceived diminished quality of these services. Thereupon, the 2014 Statistics South Africa general household survey indicated though that most (69%) households have a preference for public clinics and hospitals facilities first followed by a private doctor (29%) whenever a member falls ill [50], p. 28.…”
Section: Service Deliverysupporting
confidence: 55%
“…In the current study, the public health system was providing poor quality of care and yielding poor health outcomes due mainly to weak leadership and fragmentation of services at the implementation level. Leadership deficits and fragmentation of public healthcare services has also been observed in other South African studies [46][47][48] and research in Gauteng [49] showed that approximately 75% of randomly-selected participants indicated that they were no longer utilising public healthcare services due to the perceived diminished quality of these services. Thereupon, the 2014 Statistics South Africa general household survey indicated though that most (69%) households have a preference for public clinics and hospitals facilities first followed by a private doctor (29%) whenever a member falls ill [50], p. 28.…”
Section: Service Deliverysupporting
confidence: 55%
“…Antenatal care for women with GDM at this hospital is intensive, highly structured and follows local and international (i.e. ; WHO and NICE) policy guidelines [21].…”
Section: Settingmentioning
confidence: 99%
“…The perceived stress of effectively managing GDM through lifestyle change coupled with the fear of failure to achieve glycaemic control may trigger depressive symptoms [19]. The management of GDM is centred on glycaemic control to prevent adverse obstetric outcomes [20][21][22], while the potential impact of the diagnosis on women's psychological and emotional well-being is seldom considered in managing the condition.…”
Section: Introductionmentioning
confidence: 99%
“…[39] In SA, pregnant women with GDM are referred to the nearest secondary or tertiary hospital for management and treatment. [40] At the tertiary level, management of GDM is through counselling and health education provided by obstetricians, endocrinologists, dieticians or nurse educators. The primary form of intervention for women with GDM is lifestyle modification, which involves counselling regarding diet and physical activity.…”
Section: Cmementioning
confidence: 99%
“…A dietary meal plan is provided, which entails reduced sugar and starch intake, increased protein intake and reduced total calorie intake. [40] However, in disadvantaged settings, these lifestyle changes are difficult to adhere to owing to the high cost of healthy food and lack of understanding and social support. A more sustainable approach is to counsel patients on how to reduce the glycaemic index of staple foods.…”
Section: Cmementioning
confidence: 99%